Gated 'communities' - their lifestyle versus urban governance - Peer Smets (European Regional Science Association (ERSA), 2005)
Today there is a widespread fear of crime on a global scale. This can be seen as a response to social inequalities, social polarisation and the fragmentation of cities, which has been caused by neo-liberalism. Worldwide, an increasing number of higher income groups have looked to security measures, such as cameras, fences, walls and gates, to separate themselves from other people in the city. These physical measures, in combination with hired guards, replace the 'older' social control mechanisms, which are based on social cohesion within the community concerned. One may question whether those living in gated 'communities' indeed feel responsible for other urbanites. In other words, will such a hard closure (physically-marked segregation) lead to soft closure, reflected in social-cultural and political segregation. What is the impact of the lifestyle(s) of those living in gated communities on the dynamics of the city, urban identity and urban governance?
Keywords: 330